(untitled) (Global Conference on Medical and Health Sciences, 2026)
Augmented reality (AR) has emerged as a transformative technology in neurosurgery, offering enhanced visualization, spatial orientation, and intraoperative guidance during complex procedures such as brain tumor resection. By integrating real-time imaging data with the surgical field, AR enables surgeons to visualize critical anatomical structures and tumor boundaries with increased precision, thereby improving surgical outcomes and reducing the risk of complications.